Internationalization and the Need of Business Model Innovation - Theoretical Approach - Moema Pereira Nunes; Fernanda Kalil Steinbruch (BBR: Brazilian Business Review)
internationalization of a firm through the adoption of any entry mode may lead to the need to innovate or adapt its business model (BM) to better fit specific contexts of international markets. Even though entry modes have been deeply investigated during the last decades, the relation of business model innovation (BMI) and entry modes is a new study subject. This article assumes that the internationalization process is a trigger for innovation, and it aims to answer what are the different possibilities of BMI generated through the entry modes. The concepts of BM, BMI, and its relationship with internationalization and entry modes are investigated in this paper. Based on the literature review, a theoretical model is proposed to relate entry modes and the need of business model innovation. We identified that little is known about the relation between these subjects and applied research is required.